Angiogenic and inflammatory biomarkers for screening and follow-up in patients with pulmonary arterial hypertension. (4th July 2018) - Kylhammar, D; Hesselstrand, R; Nielsen, S; Scheele, C; Rådegran, G
Abstract : Objective : To identify circulating angiogenic and inflammatory biomarkers with potential in screening for pulmonary arterial hypertension (PAH) in systemic sclerosis (SSc), and in early diagnosis and determination of treatment response in PAH. Method : Plasma samples were taken at the time of PAH diagnosis and at treatment follow-up after a median (interquartile range) of 4 months (3–9.8 months) in idiopathic (n = 9) and SSc-associated PAH (n = 11). In patients with SSc-associated PAH, plasma samples had also been gathered a median of 2 years (0.8–3 years) before PAH diagnosis (n = 10). Additional plasma samples were retrieved at two time-points separated by a median of 12 years (10–13 years) from SSc patients who did not develop PAH (n = 10) and from controls (n = 8). Angiogenic and inflammatory biomarkers were analysed by multiplex immunoassays. Results : Plasma levels of placenta growth factor (PlGF), soluble vascular endothelial growth factor receptor-1 (sVEGFR-1), and tumour necrosis factor-α (TNF-α) were higher (p < 0.05) in SSc patients who later developed PAH than in those who did not. Plasma vascular endothelial growth factor (VEGF)-D increased (p < 0.05) in SSc patients as PAH developed. Plasma levels of PlGF, VEGF-A, VEGF-D, sVEGFR-1, interleukin-6, and TNF-α were higher (p < 0.05) in PAH than controls. There were no significant differences in circulating biomarkers between idiopathic and SSc-associated PAH. Plasma sVEGFR-1 decreased (p < 0.05) after initiating PAH-targeted treatments. Conclusions : Plasma levels of PlGF, sVEGFR-1, TNF-α, and VEGF-D have potential in screening for SSc-associated PAH. Plasma sVEGFR-1 may be a biomarker of treatment response.